2020
DOI: 10.21873/anticanres.14361
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3L Is a New Autophagy Related Prognostic Biomarker for Melanoma Patients Treated With AGI-101H

Abstract: Background/Aim: Skin melanoma belongs to the most invasive malignancies with no cure for a progressing disease. Personalized therapy would allow for the selection of patients that will benefit from treatment. For this purpose, proper predictive biomarkers must be defined. Materials and Methods: Allogeneic whole-cell gene-modified therapeutic melanoma vaccine (AGI-101H) was applied in advanced melanoma patients. Humoral responses were analyzed using SEREX, and in silico gene expression analysis in TCGA melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…The expression levels of transcripts were analyzed depending on the clinicopathological parameters, such as: sample type (primary vs. metastasis), cancer type (cutaneous melanoma vs. other), cancer localization (extremities vs. trunk vs. regional lymph node vs. head and neck vs. distant metastasis vs. cutaneous or subcutaneous tissue vs. other), gender (women vs. men), age (< 58 vs. > 58), ulceration (absent vs. present), Clark level (I vs. II vs. III-IV vs. V), Breslow depth (< 1 vs. 1-2 vs. 2.1-4 vs. > 4), mitotic rate (0-2 vs. 2-3 vs. > 4), cancer stage (0 vs. I + II vs. III + IV), M-stage (M0 vs. M1), T-stage (T0 vs. T1 + T2 vs. T3 + T4), similarly as described previously [28]. Next, from a group of 472 patients, highand low-expressing groups of RPL23AP53 were obtained using the quartile expression as a cutoff: low (< 25) and high (> 75).…”
Section: Clinical-pathological Data Analysismentioning
confidence: 52%
See 1 more Smart Citation
“…The expression levels of transcripts were analyzed depending on the clinicopathological parameters, such as: sample type (primary vs. metastasis), cancer type (cutaneous melanoma vs. other), cancer localization (extremities vs. trunk vs. regional lymph node vs. head and neck vs. distant metastasis vs. cutaneous or subcutaneous tissue vs. other), gender (women vs. men), age (< 58 vs. > 58), ulceration (absent vs. present), Clark level (I vs. II vs. III-IV vs. V), Breslow depth (< 1 vs. 1-2 vs. 2.1-4 vs. > 4), mitotic rate (0-2 vs. 2-3 vs. > 4), cancer stage (0 vs. I + II vs. III + IV), M-stage (M0 vs. M1), T-stage (T0 vs. T1 + T2 vs. T3 + T4), similarly as described previously [28]. Next, from a group of 472 patients, highand low-expressing groups of RPL23AP53 were obtained using the quartile expression as a cutoff: low (< 25) and high (> 75).…”
Section: Clinical-pathological Data Analysismentioning
confidence: 52%
“…The expression level was analyzed in the group of all patients, as the median of RPL23AP53 and separately depending on BRAF status, with mutation (MUT) and wild type (WT). Progression-free interval (PFI) and overall survival (OS) were assessed in these subgroups, similarly as described previously [28].…”
Section: Clinical-pathological Data Analysismentioning
confidence: 99%
“…Even more recently, Kwiatkowska-Borowczyk et al, (2018) revealed that immunization of patients resulted in the generation of cytotoxic CD8+ T cells specific for Aldehyde Dehydrogenase 1 Family Member A1 (ALDH1A1) along with the production of specific anti-ALDH1 antibodies [54]. Kazimierczak et al, (2020) discovered a new biological marker for monitoring melanoma immunotherapy, where there is a positive correlation between the production of antibodies to BNIP3L/NIX and the clinical outcome of melanoma patients treated with the AGI-101H vaccine [55]. Increased expression of BNIP3L is also positively correlated with patient overall survival (OS) in melanoma.…”
Section: Whole-cell Vaccinesmentioning
confidence: 99%
“…Increased expression of BNIP3L is also positively correlated with patient overall survival (OS) in melanoma. BNIP3L is induced by tumor suppressor p53 and, in response to hypoxic TME conditions, plays a crucial role in the clearance of damaged mitochondria with mitochondrial autophagy [55].…”
Section: Whole-cell Vaccinesmentioning
confidence: 99%